Framing the Rohingya Crisis in Aceh’s Local Media - Febri Nurrahmi; Aisya Syahira; Ade Oktiviyari (Mediakita, 2026)
This study examined the framing of Rohingya refugee coverage in ANTARA Aceh amid rising social tension influenced by negative narratives on social media. Guided by agenda-setting theory and Robert Entman’s framing model, it analyzed 12 online news articles from aceh.antaranews.com, supported by interviews with two ANTARA Aceh journalists. Methodologically, this study contributes by integrating framing analysis and transitivity analysis through a triangulated approach. Unlike prior studies that rely mainly on identifying framing elements, this study treats Entman’s elements as linguistic indicators to elicit frames and verifies them through transitivity, offering a more systematic analysis. The findings show that ANTARA Aceh predominantly employed a security frame, particularly through narratives of crime and social order. The issue was defined in terms of public security, law enforcement, and social disruption, such as refugee escape, smuggling, and community rejection. Causes were linked to both structural weaknesses and situational factors, while moral judgment positioned refugees as both vulnerable and problematic. The proposed solutions emphasized control, relocation, and legal enforcement. Transitivity analysis confirmed that linguistic patterns in headlines reinforced this framing. This study demonstrates how media framing is constructed and validated at the linguistic level, highlighting how a state news agency prioritizes security over humanitarian concerns.